'Εξυπνα Φαρμακευτικά Εργοστάσια - Rekkas Ventiris, Michail (Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών, 2018)
In 2011, at a large industrial exhibition in Hannover, the term "Industry 4.0" was officially mentioned (4th industrial revolution). Seven years later, the academic world as well as many companies have tried to capture what "Industry 4.0" means. A smart factory, in line with the 4th Industrial Revolution, meeting the specifications of the fourth industrial revolution, should successfully use the 8 key elements mentioned in the next paragraph. Success is directly related to productivity and efficiency. The 8 key elements of an intelligent factory are as follows: • Big data • Internet of things • 3D printing • Augmented reality • Robotic systems • Machine learning • Cloud computing • System Integration There is plenty of examples in the industry around the world, with cars in a dominant position. The pharmaceutical industry is making efforts to follow the new industry trend and there are some notable applications. The American Food and Drug Administration itself refers to the need to use new technologies in pharmaceutical processes and many of the guidelines it has issued refer to the management of a large volume of data from processes and the tendency for all separate steps in pharmaceutical production to function as a system. In more details in this master thesis the following guidelines are examined: • Continued process verification • Continuous process improvement • Data integrity • Continuous manufacturing • Real time release testing But apart from complying with the directives of the regulatory authorities, the drug industries can also have economic benefits from the technologies of the 4th Industrial Revolution. Applications like continuous manufacturing and Real Time Release Testing can be better supported with the technologies of the 4th industrial revolution. Studies from the Universities laboratories and the practical application of these ideas have shown that there are significant economic benefits.